- #1

- 392

- 13

## Homework Statement

[/B]

##\lim x\rightarrow \frac{\pi }{4} (\frac{1-\tan x}{\sin x - \cos x})##

## The Attempt at a Solution

[/B]

By assuming y = x-π/4 , the limit become :

##

\lim y\rightarrow 0 (\frac{1- \tan (y+\frac{\pi}{4})}{\sin (y+\frac{\pi}{4}) - \cos (y+\frac{\pi}{4})})

= \lim y\rightarrow 0 (\frac{1- (y + (\frac{\pi}{4})) (\frac{\tan (y+\frac{\pi}{4})}{y+(\frac{\pi}{4})})}{(y + (\frac{\pi}{4})) \frac{\sin (y+\frac{\pi}{4})}{(y + (\frac{\pi}{4}))} - \cos (y+\frac{\pi}{4})})

= (\frac{1-\frac{\pi}{4}(1)}{\frac{\pi}{4}(1)-\frac{\sqrt{2}}{2}})##

But, using the identity tan x = sin x/ cos x and by graph, I get the answer is ##-\sqrt{2}##

So, please tell me the wrong that I did..

Why can't we just use the theorem lim x-> 0 tan x/x = 1 and lim x->0 sin x/x =1 ??

I don't understand the steps to solve a trigonometric limit, because using different methods, the answer can be different